Defumação do queijo coalho utilizando a defumação líquida e um protótipo de um mini defumador - Pedral, Amanda de Lucena (2014)
Brazil has a variety of cheeses produced by handmade which has different characteristics according to the region where this cheese is produced. In the Northeast, the main artisan cheese is the coalho cheese that stands out for being a typical product of the northeastern hinterland is much used among the culinary delicacies of the region. Conventional smoking is a method used since antiquity for food preservation, currently. it is understood by smoking the process of exposing food to smoke from aromatic woods. When performed at temperatures below 30 ° C is called cold curing, hot curing and if the temperature is greater than 30 °C. With this technique an aroma, flavor and color typical of smoked products which can also produce preservative effect arises. Conventional smoking is being increasingly replaced by the use of liquid smoke flavoring or "liquid smoke" as it is also known. The liquid smoke flavoring is used to replace natural smoke vapors as a means to develop flavor and color characteristics of smoked as well as an antioxidant and bactericidal products. The aim of this study was to develop the coalho cheese smoked from the liquid smoking and using a mini smoker, in order to obtain a new product, checking physical chemical changes, sensory acceptance and evaluate the presence of Polycyclic Aromatic Hydrocarbons (PAH). Using industrial coalho cheese was held conventional processes using a mini smoker smoking and liquid smoking using the liquid smoke. The smoked curd cheeses were stored for 28 days in packs of high density polyethylene in vacuum exhibitors at 5 ± 1 ° C. The physico-chemical analyzes showed significant differences in the parameters during storage of moisture, pH, acidity, phenols and color. Regarding the texture profile analysis, the samples showed significant differences for hardness and chewiness, which showed a positive correlation between these two parameters. Sensory analysis indicated that the products had good acceptability and the smoked cheese using the mini smoker got best purchase intent. Although the coalho cheese be a semigordo or fat cheese and PAH possess lipophilic behavior, no evidence of PHA were found in the samples analyzed. We conclude that the use of smoking, both with mini smoker as with liquid smoke, added value to coalho cheese, it is possible to develop a new product, with positive organoleptic and nutritional characteristics, and sensory acceptability by consumers and absence of carcinogenic compounds.